2019
DOI: 10.1007/s11606-019-05312-z
|View full text |Cite
|
Sign up to set email alerts
|

Annual Spending per Patient and Quality in Hospital-Owned Versus Physician-Owned Organizations: an Observational Study

Abstract: BACKGROUND: Recent studies that compared patient spending in hospital-owned physician practices versus physician-owned groups did not compare quality of care. Past studies had incomplete measures of physicianhospital integration, or lacked patient-level data. OBJECTIVE: To measure the association between physician-hospital integration and both spending and quality using patient-level data and explicit physicianhospital contracting information. DESIGN: Retrospective review of claims data from 2014 through 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
(42 reference statements)
1
34
0
Order By: Relevance
“…35 Similarly, Ho et al found that commercially insured patients incurred spending which was 5.8 percentage points higher when treated by doctors in hospital-owned versus physician-owned practices. 24 In contrast, we found that financial integration was asso- quality. Some studies have found that care processes in financially integrated systems are better than those in independent practices, for example, finding higher levels of medication adherence and lower medication error rates.…”
Section: Ta B L E 5 Linear Regression Estimates Of Association Betweementioning
confidence: 62%
See 1 more Smart Citation
“…35 Similarly, Ho et al found that commercially insured patients incurred spending which was 5.8 percentage points higher when treated by doctors in hospital-owned versus physician-owned practices. 24 In contrast, we found that financial integration was asso- quality. Some studies have found that care processes in financially integrated systems are better than those in independent practices, for example, finding higher levels of medication adherence and lower medication error rates.…”
Section: Ta B L E 5 Linear Regression Estimates Of Association Betweementioning
confidence: 62%
“…Financial integration (which we define as the degree of financial management and planning across operating units, including the level of horizontal and vertical integration present 13 ) may improve care coordination by bringing providers together within the same organizational structure, but could potentially increase costs without providing clinical benefits. 14 Though providers claim that financial integration is necessary to improve the functions that produce better clinical outcomes, 15 research shows mixed effects on clinical quality and outcomes, [16][17][18][19][20][21][22] alongside higher prices and spending, [23][24][25][26][27][28][29][30] and increased premiums. 31 Recent work found moderately worse patient experience outcomes after financial integration, 19 and little association between health system affiliation and the adoption of quality-focused care delivery and payment reforms.…”
Section: Introductionmentioning
confidence: 99%
“…We identified all claims from primary care physicians (PCP) and used these claims to attribute as many patients as possible to a PCP who was assumed to be responsible (directly or through referrals) for the majority of the patient's care. The method for attribution is explained elsewhere in detail (Ho et al 2019), and involves attributing each patient to the primary care physician they visited most in a 24-month window including each calendar year of data and the additional 12 months closest to it. Each provider submits their specialty when they request a provider record/credentialing with BCBSTX.…”
Section: The Bcbstx Claims Datamentioning
confidence: 99%
“…Fourth, we estimate a regression of annual spending for each BCBSTX member on the ownership type of the attributed PCP's practice as determined by their TIN. This regression was estimated in a previous study which sought to compare annual health spending and quality of care for patients treated by doctors in hospital-owned versus physicianowned practices (Ho et al 2019). We compare regression results using the ownership type as defined by BCBSTX versus a regression where ownership type is inferred based on MD-PPAS TINs and our internet search of TIN legal names.…”
Section: Merging and Descriptive Analysismentioning
confidence: 99%
“…In this issue of JGIM, Ho et al use an observational study design to compare spending and quality of care among patients treated at hospital-owned physician practices and patients treated at independent physician practices in Texas [4]. The authors improve upon the standard survey-or claimsbased approaches to measuring vertical integration, instead going directly to the source and using records maintained by Blue Cross Blue Shield of Texas on the contracts negotiated with hospitals and physicians.…”
mentioning
confidence: 99%